Dynamics of insurance policies for sporting events: COVID-19 - Ijuo, I.; Kayode, O. (2020)
It is a fact that sport plays a pivotal role to promote education, health, intercultural dialogue, and the individual development, regardless of an individual's gender, race, age, ability, religion, political affiliation, sexual orientation, or socioeconomic background but, the effect of the on-going coronavirus pandemic has created ravaging economic challenges in sporting industry, we now see empty stadiums, majority of sporting games/events have been suspended, cancelled or postponed indefinitely, while others have been nullified, this is a critical moment for sport lovers and administrators all-round the globe. Whilst the world seeks to deal with the economic effect of the pandemic, this article explores: the economic effects the lockdown has had in the sports industry; obtainable insurable risks covers in the sporting industry; the extent insurance companies can be liable to sport insurance policy holders, and concludes with a clarion call for sport organizers to insure against catastrophes.